The application of covalent organic frameworks in Lithium-Sulfur batteries: A mini review for current research progress - Zhuo Wang; Zhuo Wang; Fei Pan; Qi Zhao; Menglan Lv; Bin Zhang (Frontiers in Chemistry, 2022)
Recently, how to enhance the energy density of rechargeable batteries dramatically is becoming a driving force in the field of energy storage research. Among the current energy storage technologies, the lithium-sulfur (Li-S) batteries are one of the most promising candidates for achieving high-capacity and commercial batteries. The theoretical energy density of Li-S batteries reaches to 2,600 Wh kg−1 with the theoretical capacity of 1,675 mA h g−1. Therefore, Li-S batteries are considered as the great potential for developing future energy storage technology. However, some of problems such as Li dendrites growth, the shuttle effect of sulfides and the electronic insulation feature of sulfur, have brought obstacles to the development of Li-S batteries. The covalent organic frameworks (COFs) are a series of porous materials with different topological structures, which show the versatile characteristics of high specific surface area, permanent pores, ordered porous channels and tunable internal structure. Potentially, their ordered channels and extended conjugated frameworks could facilitate rapid Li-ion diffusion and electron transport for the remarkable rate capability. On the basis of these merits, the COFs become the potential electrode materials to solve the above serious problems of Li-S batteries. In this mini review, we summarize the research progress of COFs utilized as electrode materials in the Li-S batteries, including the cathode, separator and anode materials. Accordingly, the outlook of COFs as electrodes for future development in Li-S batteries is also given.